If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 + 4x + 15 = 90 Reorder the terms: 67 + 15 + 4x = 90 Combine like terms: 67 + 15 = 82 82 + 4x = 90 Solving 82 + 4x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-82' to each side of the equation. 82 + -82 + 4x = 90 + -82 Combine like terms: 82 + -82 = 0 0 + 4x = 90 + -82 4x = 90 + -82 Combine like terms: 90 + -82 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| X^2-Y^2-6X-4Y+4=0 | | -6a^6+4a^5-2a^4= | | -2-5cos(x)+6sin^2x=0 | | 2(X+X-7)=3(X+9+X+2+X-7) | | 5x+8x-20=0 | | -2+0.9+0.5(-2)=-2.1 | | (X)(-x)(-2x)= | | 3X^2-XY=0 | | (X)(2x)(y)= | | (5x)(2x)(x)= | | 6-2x=2(1x+3) | | X=5s | | 2(7-x)+5(x+1)=10(1+x)-9(x+1) | | 400=49.91x | | 9(2x+3)=18x+27 | | 5.70=0.05x+1.70 | | 14x+43-25x=229 | | y=0.05(27)+1.70 | | 5x+8x+3x-4y= | | .25x+.5(71-x)=22 | | 8-4x=2(2x+4) | | 94-4p-6p=-1 | | 5x=100y | | 2x+(x-56)=3x | | 9r-28=-3+4r | | X-9=4x+6 | | 7r-11=-23+9t | | -2x^2+13=-43 | | 3x+3=7+7x | | 7d+40=10 | | 4x+2x+3=6x | | W^2+13w=608 |